Advanced Neuroimaging in Stroke Patient Selection for Mechanical Thrombectomy: A Systematic Review and Meta-Analysis. Issue 12 (December 2018) - Tsivgoulis, Georgios; Katsanos, Aristeidis H.; Schellinger, Peter D.; Köhrmann, Martin; Caso, Valeria; Palaiodimou, Lina; Magoufis, Georgios; Arthur, Adam; Fischer, Urs; Alexandrov, Andrei V.
Abstract : Background and Purpose—: There is clinical equipoise about the use of advanced imaging for selecting acute ischemic stroke patients eligible for mechanical thrombectomy (MT) during the first 6 hours from symptom onset. However, accumulating evidence indicates that advanced neuroimaging represents an invaluable and time-independent prognostic factor. Methods—: We performed a systematic review and meta-analysis of available randomized clinical trials to evaluate the impact of patient selection with advanced neuroimaging on the 3-month: (1) functional independence (modified Rankin Scale score, 0–2), (2) favorable functional outcome (modified Rankin Scale scores, 0–1), (3) all-cause mortality, and (4) functional improvement (assessed with ordinal analysis of the modified Rankin Scale-scores). We compared patients with perfusion imaging documented penumbra to patients who did not have documented penumbra or perfusion imaging. Results—: Among the 10 eligible randomized clinical trials (2227 total patients, mean age: 67 years), 5 studies reported the use of advanced imaging. Studies using advanced neuroimaging showed higher treatment effects of MT on 3-month functional independence (odds ratio [OR], 3.79; 95% CI, 2.71–5.28 versus OR, 1.89; 95% CI, 1.52–2.35; P for subgroup differences <0.001), favorable functional outcome (OR, 3.16; 95% CI, 1.94–5.14 versus OR, 1.75; 95% CI, 1.30–2.34; P for subgroup differences=0.04), and functional improvement (common OR, 2.66; 95% CI, 1.95–3.63 versus common OR, 1.60; 95% CI, 1.32–1.95; P for subgroup differences=0.007) compared with studies using conventional neuroimaging. The pooled rate of successful reperfusion after MT was higher in studies with advanced neuroimaging ( P for subgroup differences=0.003). No difference in the mortality and symptomatic intracranial hemorrhage rates was found between the 2 groups. No evidence of heterogeneity was documented in all reported analyses. Conclusions—: The present indirect comparisons indicate that acute ischemic stroke patient selection for MT using advanced neuroimaging appears to be associated with improved clinical outcomes. The use of advanced neuroimaging for both the selection and prediction of prognosis for MT candidates should not depend on the elapsed time from symptom onset. Abstract : Supplemental Digital Content is available in the text.